2020
DOI: 10.32607/actanaturae.10915
|View full text |Cite
|
Sign up to set email alerts
|

Rare Cases of IDH1 Mutations in Spinal Cord Astrocytomas

Abstract: A low occurrence rate of spinal cord gliomas (4.3% of primary and glial CNS tumors) and the associated difficulties in building statistically significant cohorts of patients considerably slow down the development of effective approaches to the treatment of spinal cord tumors compared to brain tumors. Despite our extensiveknowledge regardingIDHmutations in intracranial tumors, mutations of this gene in spinal cord astrocytomas remain poorly understood. In thisstudy, we report on five cases of identified mutatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 12 publications
(16 reference statements)
0
6
0
Order By: Relevance
“…Even though IDH-mutant spinal gliomas are very rare, several spinal gliomas with variants other than IDH1 R132H have been reported, and IDH1 R132H mutations are probably not so prevalent in spinal gliomas. Konovalov et al [ 48 ] reported 5 cases of spinal cord astrocytomas with IDH mutations: 2 had IDH1 R132H mutations, while 1 had an IDH1 R132G mutation. In addition, the remaining 2 cases had translocations at positions 82 (Arg → Lys, R82K) and 76 (Ile → Thr, I76T) of the IDH1 gene, which had never been described in intracranial gliomas in the past.…”
Section: The Clinical Features and Genetic Findings Of Intramedullary...mentioning
confidence: 99%
“…Even though IDH-mutant spinal gliomas are very rare, several spinal gliomas with variants other than IDH1 R132H have been reported, and IDH1 R132H mutations are probably not so prevalent in spinal gliomas. Konovalov et al [ 48 ] reported 5 cases of spinal cord astrocytomas with IDH mutations: 2 had IDH1 R132H mutations, while 1 had an IDH1 R132G mutation. In addition, the remaining 2 cases had translocations at positions 82 (Arg → Lys, R82K) and 76 (Ile → Thr, I76T) of the IDH1 gene, which had never been described in intracranial gliomas in the past.…”
Section: The Clinical Features and Genetic Findings Of Intramedullary...mentioning
confidence: 99%
“…Mutations in the isocitrate dehydrogenase ( IDH ) gene are common in intracranial Grades 2 and 3 astrocytomas; however, their prevalence is rarer in intramedullary astrocytomas ( 115 ). IDH1 and IDH2 are enzymes responsible for conversion of isocitrate in the citric acid cycle, and mutations result in accumulation of R-2-hydroxyglutarate ( 116 ).…”
Section: Molecular Landscapementioning
confidence: 99%
“…This metabolite competitively inhibits histone demethylases, resulting in broad epigenetic changes to DNA methylation and gene expression ( 83 ). IDH mutations can be used intracranially as both a diagnostic marker to distinguish diffuse from pilocytic astrocytomas, given its rare incidence in pilocytic astrocytomas, and as a prognostic marker, with IDH-mutant tumors having a more favorable prognosis compared to wild-type tumors ( 115 , 117 ).…”
Section: Molecular Landscapementioning
confidence: 99%
See 1 more Smart Citation
“…Although several cases of spinal IDH -mutant astrocytomas and spinal oligodendrogliomas have been reported, they are extremely rare [ 27 , 28 ]. Hemispheric gliomas, such as diffuse hemispheric glioma, H3 G34-mutant, and infant-type hemispheric glioma, are also extremely rare.…”
Section: Diffuse Astrocytic Tumors Including Adult-type Diffuse Gliom...mentioning
confidence: 99%